ANTUSIASME MASYARAKAT DESA DANGIN PURI KANGIN TERHADAP KEBERADAAN BANK SAMPAH WIJAYA KUSUMA - Erik Saputra, I Kadek; Nugroho, Wahyu Budi; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
Trash bank is one of the organizations in the environmental field. The existence of trash bank in Dangin Puri Kangin village is appreciated by people there. It can be seen by the Dangin Puri Kangin people’s enthusiasm in joining trash bank program. The problems in this study are how is the mechanisms to save in Trash Bank which is located in Wijaya Kusuma, why do the people interested to invest/saving in trash bank in Wijaya Kusuma, and the what is the benefits to invest/saving in Trash Bank in Wijaya Kusuma. Furthermore, the social exchange theory from George Caspar Homans is used in this study. Homans divided his theory into six propositions. The result of this study is three propositions by Homans found, they are the success proposition, the stimulus proposition, and the value proposition. Furthermore, there are five people’s mechanisms of utilizing trash through 3R such as sorting trash, bringing trash to trash bank, weighing, recording the amount of trash according to the weight and kind, and the trash weighing record can make money. The reason people are interested in saving in Wijaya Kusuma Trash Bank is money, and the benefits gained after saving at Wijaya Kusuma Trash Bank are economic, environmental, and educational benefits. Keywords: Trash Bank, People's Enthusiasm